(untitled) (Argos, 2025)
The reception of the old comedy generally overcomes the strict frame of the dramatic genres, and makes clear the interest of later periods in this genre. This paper focuses on the reception of comedy in one of the most creative genres of the Greek literature in the imperial age, that of epistolography. It deals with a short letter from Aelian’s farmers’ letters, which follows the model of some passages of an Aristophanic comedy. Besides these passages, the Old Oligarch provides also a considerable part of the linguistic frame where the epistolographical discourse finds its place.